PERAN DANA DESA DALAM MENGURANGI KEMISKINAN DAN MENINGKATKAN INKLUSI SOSIAL PADA PETANI PENGGARAP DESA AKA-AKAE KABUPATEN SIDENRENG RAPPANG - Kamal, Afrah Namirah; JS, Romi Nugraha; Taufiq, Muhammad (Paser Institute Of Accounting and Finance, 2025)
The aim of writing this thesis is to determine the role of village funds in reducing poverty and increasing social inclusion as well as finding out the supporting and inhibiting factors for sharecroppers in Aka-Akae Village, Sidenreng Rappang Regency. This research method is a qualitative phenomenological approach with data collection techniques by means of interviews, observation and documentation. The informants were determined through purposive sampling and snowball sampling. The theory used is the welfare state theory, namely that the state is responsible for the welfare of its citizens. This research shows the results that the use of village funds in reducing poverty in Aka-Akae Village consists of four programs, namely organic fertilizer education accompanied by outreach, 10 kg rice assistance, and Direct Cash Assistance (BLT), these four things still receive a poor response from poor sharecroppers because they have not been able to get farmers out of the trap of poverty. Apart from that, the role of village funds in increasing social inclusion is also not effective because sharecroppers are still excluded due to the lack of active involvement of sharecroppers in Musrembang, lack of empowerment programs for women, and lack of women's involvement in Musrembang.